Analisis Akurasi Dimensi Prototipe Cetakan Cutting Tools Insert Tri Angle Menggunakan Proses Pencetakan 3D Berbahan PETG - Muhammad Sobron Yamin Lubis; Raylan Alexander; Gerard Theodorus; Salma Khaula Bazla; Muhamad Zaki Adika; Rifqi Andika Putra; Silvi Ariyanti; Muhammad Zulkarnain (CV. IRA PUBLISHING, 2025)
This study aims to analyze the dimensional accuracy of tri-angle cutting tool insert mold prototipes produced via PETG-based 3D printing. The printing process was carried out with predetermined printing parameters, and the resulting prototipes were measured and compared with the original design dimensions. The evaluation focused on the main dimensions of the insert to determine dimensional deviation and accuracy. The results indicate that PETG 3D printing can produce mold prototipes with satisfactory dimensional accuracy, though minor deviations were observed due to printing parameters and material characteristics. This study is expected to serve as a reference for using 3D printing technology as an efficient, cost-effective alternative for manufacturing cutting tool mold prototipes.